Kebutuhan Praktik Keperawatan Keluarga: Tinjauan Literatur - Aco Mursid; Erviana Erviana; Muhammad Irwan; Indrawati Indrawati; Evidamayanti Evidamayanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: The purpose of this study was to synthesize literature related to family nursing practice to become an evidence-based practice guideline. Methods: A literature analysis was carried out by synthesizing research articles from international publications. Results: 13 synthesized articles. Two themes emerged from the analysis, namely: 1) the development of education and learning systems, and 2) involving family members or caregivers in nursing practice. Conclusion: Any findings needed. Applying the results of this study is considered to be a guide for practitioners and academics in carrying out the family nursing practice. The results of this study put forward a special approach that can be carried out by higher nursing education institutions and health service providers